Attitude of Pig Breeders To The Impact Of Miningitis Streptococcus suis (MSs) Disease at Abiansemal District of Badung Regency - N. I. K., Noviyanti; Suparta, I N.; Ariana, I N. T (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
Pig is one of potential commodity to develop some things must be pay more attention in  this case are pen, feed, disease etc. One of disease that often infected pig is Miningitis Streptococcus suis (MSs), is also infected human being. This research aims to  know attitud to the impact of Miningitis Streptococcus suis (MSs) disease at Abiansemal districk of Badung regency. The research conducted for 3 months. Ellection of location and determination of respondent used was Purposive Sampling which means sample was taken randomly. The number of respondents mean 35 pig breeders. Analysis of data used was descriptive qualitative analysis and correlation test spearman. The result of the research showed that attitude of pig breeders to the impact of Minigitis Streptococcus suis (MSs) is in the category positive. Factors related the attitude of the breeders to the impact of Minigitis Streptococcus suis (MSs) disease at Abiansemal district of Badung regency such as education, livestock owning and perception had significant corelationn (P<0,05) to the impact of Miningitis Streptococcus suis (MSs) disease . Key words: pig breeders, Miningitis Streptococcus suis (MSs), attitude